2009
DOI: 10.1667/rr1632.1
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocotrienol Ameliorates Intestinal Radiation Injury and Reduces Vascular Oxidative Stress after Total-Body Irradiation by an HMG-CoA Reductase-Dependent Mechanism

Abstract: Analogs of vitamin E (tocols) are under development as radioprophylactic agents because of their high efficacy and lack of toxicity. Gamma-tocotrienol (GT3) is of particular interest because, in addition to being an antioxidant, it also inhibits 3-hydroxy-3-methylglutaryl-coenzyme A (HMGCoA) reductase and accumulates to greater extent in endothelial cells than other tocols. We addressed in vivo whether HMG-CoA reductase inhibition contributes to the radioprotection conferred by GT3. Groups of mice were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
165
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(170 citation statements)
references
References 46 publications
5
165
0
Order By: Relevance
“…Similarly, only triglyceride levels were reduced in carbon tetrachloride-induced fatty liver in rats (Yachi et al 2010). In addition to cholesterol-related metabolism, Berbee et al (2009) showed that c-T3 improved post-irradiation survival and decreased radiation-induced vascular oxidative stress after a total-body irradiation. The effect of c-T3 could be eliminated by mevalonate, the product of the reaction catalyzed by HMGCR, suggesting that the protective role of c-T3 was through an HMGCR-dependent mechanism.…”
Section: Anti-cancer Effects Of Tocotrienolsmentioning
confidence: 95%
“…Similarly, only triglyceride levels were reduced in carbon tetrachloride-induced fatty liver in rats (Yachi et al 2010). In addition to cholesterol-related metabolism, Berbee et al (2009) showed that c-T3 improved post-irradiation survival and decreased radiation-induced vascular oxidative stress after a total-body irradiation. The effect of c-T3 could be eliminated by mevalonate, the product of the reaction catalyzed by HMGCR, suggesting that the protective role of c-T3 was through an HMGCR-dependent mechanism.…”
Section: Anti-cancer Effects Of Tocotrienolsmentioning
confidence: 95%
“…Because of relatively potent antioxidant properties and lack of performance-degrading side effects, vitamin E analogs, collectively referred to as tocols, are considered to be attractive candidate agents for radioprotection. In recent years, various tocols have been tested for their radioprotective potential (Berbee et al 2009;Kumar et al 2002;Singh et al 2006). Important structural and functional differences exist between the different tocols.…”
Section: Introductionmentioning
confidence: 99%
“…In a direct side-by-side comparison, Kumar et al demonstrated that GT3 is superior to a-tocopherol in reducing lethality after total body irradiation (TBI) in mice (Kumar et al 2008). Subsequent studies have shown that the radioprotective properties of GT3 not only depend on its antioxidant action but also on the modulation of endothelial cell function (Berbee et al 2009). Endothelial dysfunction is a prominent feature of early as well as late radiation injury and has been shown to play an important role in the pathogenesis of radiation toxicity in various organ systems (Baker and Krochak 1989;Hopewell et al 1993;Jaenke et al 1993;Lyubimova and Hopewell 2004;Maj et al 2003;Paris et al 2001;Rezvani et al 1995;Wang et al 2002Wang et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations